2021
DOI: 10.1097/md.0000000000026479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a food preparation program on dietary well-being for stroke patients with dysphagia

Abstract: Background: Dysphagia is one of the common issues observed in patients with stroke. Stroke patients with dysphagia have to eat blended food or similar types of food for each meal, resulting in dietary dissatisfaction. The purpose of this study was to investigate the effects of a food preparation program on dietary well-being for stroke patients with dysphagia. Methods: This study was a pilot randomized clinical trial. Twenty-two patients were assigned randomly into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 37 publications
(75 reference statements)
0
38
0
1
Order By: Relevance
“…It assesses 10 QoL concepts; eight of which are dysphagia-related QoL (food selection, burden, mental health, social functioning, fear, eating duration, eating desire, communication) and two pertaining to general QoL (sleep and fatigue). [ 169 ] 1 [ 78 ] Abbreviations : AQoL-4D Assessment of Quality of Life-4 Dimension, AQoL-6D Assessment of Quality of Life-6 Dimension, AQoL-8D Assessment of Quality of Life-8 Dimension, CLDQ Chronic Liver Disease Questionnaire, EORTC European Organization for Research and Treatment of Cancer, EORTC-QLQ-BR23 EORTC-Breast Cancer Module, EORTC-QLQ-C30. EORTC- General Cancer Questionnaire, EORTC-QLQ-H&N35 EORTC- Head & Neck Cancer Module, EORTC-QLQ-OES18 EORTC- Oseophageal Cancer Module, EQ-5D-VAS EuroQol– 5 Dimension Visual Analog Scale, EQ-5D-3L 3-level EuroQol– 5 Dimension, EQ-5D-5L 5-level EuroQol– 5 Dimension, FAACT Functional Assessment of Anorexia/Cachexia Treatment, FACT-B The Functional Assessment of Cancer Therapy – Breast, FACT-C Functional Assessment of Cancer Therapy – Colorectal, FACT-G Functional Assessment of Cancer Therapy – General, FACT-G7 Functional Assessment of Cancer Therapy – General – 7 Item Version, IWQOL-Lite Impact of Weight on Quality of Life-Lite, KDQOL-SF Kidney Disease Quality of Life Short Form, KOOS Knee Injury and Osteoarthritis Outcome Score, MiniAQLQ Mini Asthma Quality of Life Questionnaire, MLHFQ Minnesota Living With Heart Failure Questionnaire, MSQoL-54 Multiple Sclerosis Quality of Life-54, NHP Nottingham Health Profile, PAC-QoL Patient Assessment Of Constipation Quality of Life, PAN26 EORTC Pancreatic Cancer Module, PDQ-39 The Parkinson's Disease Questionnaire, PedsQoL Pediatric Quality of Life Inventory, POMS2 Profile of Mood States Second Edition, PROMIS SF Patient Reported Outcomes Measurement Information System – Short Form, QoL-B Quality of Life Questionnaire-Bronchiectasis, QUALEFFO-41 Quality of Life Questionnaire of the European Foundation for Osteoporosis, QUALIDEM Quality of Life for People with Dementia, RV-DQOL Revised Version of Diabetes Quality of Life Instrument, SF-12 Short-Form 12-Item Health Survey, SF-36 Short-Form 36-Item Health Survey, SGRQ St. George's Respiratory Questionnaire, SIP Sickness Impact Profile, SWAL-QOL Swallowing Quality of Life questionnaire, WHOQoL-BREF World Health Organization Quality of Life Scale-BREF …”
Section: Resultsmentioning
confidence: 99%
“…It assesses 10 QoL concepts; eight of which are dysphagia-related QoL (food selection, burden, mental health, social functioning, fear, eating duration, eating desire, communication) and two pertaining to general QoL (sleep and fatigue). [ 169 ] 1 [ 78 ] Abbreviations : AQoL-4D Assessment of Quality of Life-4 Dimension, AQoL-6D Assessment of Quality of Life-6 Dimension, AQoL-8D Assessment of Quality of Life-8 Dimension, CLDQ Chronic Liver Disease Questionnaire, EORTC European Organization for Research and Treatment of Cancer, EORTC-QLQ-BR23 EORTC-Breast Cancer Module, EORTC-QLQ-C30. EORTC- General Cancer Questionnaire, EORTC-QLQ-H&N35 EORTC- Head & Neck Cancer Module, EORTC-QLQ-OES18 EORTC- Oseophageal Cancer Module, EQ-5D-VAS EuroQol– 5 Dimension Visual Analog Scale, EQ-5D-3L 3-level EuroQol– 5 Dimension, EQ-5D-5L 5-level EuroQol– 5 Dimension, FAACT Functional Assessment of Anorexia/Cachexia Treatment, FACT-B The Functional Assessment of Cancer Therapy – Breast, FACT-C Functional Assessment of Cancer Therapy – Colorectal, FACT-G Functional Assessment of Cancer Therapy – General, FACT-G7 Functional Assessment of Cancer Therapy – General – 7 Item Version, IWQOL-Lite Impact of Weight on Quality of Life-Lite, KDQOL-SF Kidney Disease Quality of Life Short Form, KOOS Knee Injury and Osteoarthritis Outcome Score, MiniAQLQ Mini Asthma Quality of Life Questionnaire, MLHFQ Minnesota Living With Heart Failure Questionnaire, MSQoL-54 Multiple Sclerosis Quality of Life-54, NHP Nottingham Health Profile, PAC-QoL Patient Assessment Of Constipation Quality of Life, PAN26 EORTC Pancreatic Cancer Module, PDQ-39 The Parkinson's Disease Questionnaire, PedsQoL Pediatric Quality of Life Inventory, POMS2 Profile of Mood States Second Edition, PROMIS SF Patient Reported Outcomes Measurement Information System – Short Form, QoL-B Quality of Life Questionnaire-Bronchiectasis, QUALEFFO-41 Quality of Life Questionnaire of the European Foundation for Osteoporosis, QUALIDEM Quality of Life for People with Dementia, RV-DQOL Revised Version of Diabetes Quality of Life Instrument, SF-12 Short-Form 12-Item Health Survey, SF-36 Short-Form 36-Item Health Survey, SGRQ St. George's Respiratory Questionnaire, SIP Sickness Impact Profile, SWAL-QOL Swallowing Quality of Life questionnaire, WHOQoL-BREF World Health Organization Quality of Life Scale-BREF …”
Section: Resultsmentioning
confidence: 99%
“…Knowing how to select and prepare dietary recommendations has been established as a core educational component through a Delphi method with patients, caregivers, and clinicians (Ghaddar et al., 2022), and having access to educational resources may increase confidence and reduce associated burden (Rangira et al., 2022). Indeed, caregivers in prior studies have indicated wanting modified food recipes (Howells et al., 2021b), and a recent pilot randomised clinical trial involving 22 stroke patients found that attending a 6‐week food preparation program (i.e., performing oral motor exercises, identifying thickeners and food textures, practising meal preparation) was associated with better self‐perceived dietary and psychosocial well‐being (Lin et al., 2021). An additional consideration regarding the development of training and education materials in Singapore is the issue of language.…”
Section: Discussionmentioning
confidence: 99%
“…Jednotlivá šetření byla nejčastěji prováděna v nemocničním prostředí (Byeon, 2020;Carlaw et al, 2011;Fu et al, 2022;Huppertz et al, 2022;Kim et al, 2019;Martindale, Stephenson a Pownall, 2019;Moon et al, 2018;Silbergleit et al, 2012;Tan et al, 2022;Zhang et al, 2016;Zhao et al, 2019), ať už v rámci neurologického oddělení (Ickenstein et al, 2010;Lin et al, 2021;Ünlüer et al, 2019), tak v rámci rehabilitačního oddělení (Sproson et al, 2018;Shao et al, 2022;Deok a Doo, 2017;Kim et al, 2020;Kang et al, 2012;Zhen et al, 2017). Druhým nejčastějším místem, kde pacienti byli zkoumáni, byla rehabilitační centra a rehabilitační kliniky.…”
Section: Výstupy K Vedlejší Rešeršní Otázceunclassified